2007
DOI: 10.1111/j.1365-2958.2007.05613.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal toxin–antitoxin loci can diminish large‐scale genome reductions in the absence of selection

Abstract: SummarySuperintegrons (SIs) are chromosomal genetic elements containing assemblies of genes, each flanked by a recombination sequence (attC site) targeted by the integron integrase. SIs may contain hundreds of attC sites and intrinsic instability is anticipated; yet SIs are remarkably stable. This implies that either selective pressure maintains the genes or mechanisms exist which favour their persistence in the absence of selection. Toxin/antitoxin (TA) systems encode a stable toxin and a specific, unstable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
156
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(162 citation statements)
references
References 78 publications
6
156
0
Order By: Relevance
“…However, it is still under debate whether these modules are acquired to gain fitness under stress conditions (57) or to protect the cell from toxic effects after the curing of plasmids harboring addiction modules (58). As a corollary to the mechanism used by F plasmid to ensure its presence in all of the progenies of the host, the chromosomal toxin-antitoxin (TA) modules guard against the deletion of important genomic loci (59). Noticeably, eptABCD operon is flanked by two of the three TA modules present in M. smegmatis to prevent loss of the operon (60).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still under debate whether these modules are acquired to gain fitness under stress conditions (57) or to protect the cell from toxic effects after the curing of plasmids harboring addiction modules (58). As a corollary to the mechanism used by F plasmid to ensure its presence in all of the progenies of the host, the chromosomal toxin-antitoxin (TA) modules guard against the deletion of important genomic loci (59). Noticeably, eptABCD operon is flanked by two of the three TA modules present in M. smegmatis to prevent loss of the operon (60).…”
Section: Discussionmentioning
confidence: 99%
“…A similar role in the stabilization of genomic islands was proposed for T-A systems. It was observed that chromosomally encoded T-A systems stabilized neighboring regions of the genome (104). It is rather enigmatic that some genomes have an abundance of R-M components.…”
Section: Stabilization Of Genomic Islandsmentioning
confidence: 99%
“…For example, the chromosomal integrons in different Vibrio species are much larger (some carry 4200 cassettes) and more diverse. Many carry toxin-antitoxin systems (for example, Rowe-Magnus et al, 2003;Szekeres et al, 2007;reviewed in Cambray et al, 2010), some carry their own promoters or have 41 open reading frame, and ORFans are prevalent. Interestingly, however, in cases where the function can be inferred it appears that the gene products produced from the cassettes are often involved in interactions with the environment that may be subject to rapid change (for example, functions associated with host interactions and virulence, interaction with phages and biofilm formation).…”
Section: Evolutionary Dynamics Of Integronsmentioning
confidence: 99%